2017
DOI: 10.1186/s13017-017-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

The Global Alliance for Infections in Surgery: defining a model for antimicrobial stewardship—results from an international cross-sectional survey

Abstract: BackgroundAntimicrobial Stewardship Programs (ASPs) have been promoted to optimize antimicrobial usage and patient outcomes, and to reduce the emergence of antimicrobial-resistant organisms. However, the best strategies for an ASP are not definitively established and are likely to vary based on local culture, policy, and routine clinical practice, and probably limited resources in middle-income countries. The aim of this study is to evaluate structures and resources of antimicrobial stewardship teams (ASTs) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 19 publications
0
37
0
2
Order By: Relevance
“…[20,21] To help students with positive attitudes towards reporting ADR in their future practice, there is a need to include training in ADR and PV in their curricula [23] to improve the clinical outcomes and promote the rational use of drugs. [24][25][26] More than half of the study population strongly agreed that ADR reporting should be made mandatory for professionals, indicating that students have positive perception towards PV and ADR reporting. The present study also found out that information not being provided by patients and weak promotional activities from the authorities was the major reasons that led to the failure in reporting ADR.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21] To help students with positive attitudes towards reporting ADR in their future practice, there is a need to include training in ADR and PV in their curricula [23] to improve the clinical outcomes and promote the rational use of drugs. [24][25][26] More than half of the study population strongly agreed that ADR reporting should be made mandatory for professionals, indicating that students have positive perception towards PV and ADR reporting. The present study also found out that information not being provided by patients and weak promotional activities from the authorities was the major reasons that led to the failure in reporting ADR.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-based programs dedicated to improving antibiotic use, commonly referred to as Antimicrobial stewardship programs (ASPs), can both optimize the treatment of infections and minimize adverse events associated with antibiotic use and AMR [44,45]. Every hospital worldwide should utilize the existing resources to create an effective multidisciplinary team.…”
Section: Appropriate Management Of Infections Across the Surgical Patmentioning
confidence: 99%
“…Every hospital worldwide should utilize the existing resources to create an effective multidisciplinary team for combating AMR. The best strategies for combating AMR are not definitively established and are likely to vary based on local culture, policy, organization, and routine clinical practice despite several guidelines on the topic [44].…”
Section: Developing New Antimicrobial Agents Increasing Antimicrobialmentioning
confidence: 99%
“…Furthermore, because medical professionals have already established their knowledge, attitudes, and behaviours about antibiotic use, it is difficult to change their deeply established views and practice patterns. 2 The necessity of improving awareness of the need for optimising antibiotics use, both for prophylaxis and therapy, has become increasingly urgent.…”
Section: The World Antimicrobial Resistance Nationally Internationallmentioning
confidence: 99%
“…However if surgeons around the world participate in this global fight and demonstrate awareness of the major problem of antimicrobial resistance, they will be a pivotal element in this fight. 2 The Global Alliance for Infections in Surgery and the World Society of Emergency Surgery have promoted a coalition that should call for increased awareness and action across all surgical departments worldwide in order to combat AMR. This coalition will be able to join all the surgical scientific societies interested in combating AMR in the world.…”
Section: The World Antimicrobial Resistance Nationally Internationallmentioning
confidence: 99%